The Influence of Cellulose-Type Formulants on Anti-Candida Activity of the Tyrocidines - Yasamin Masoudi; Wilma van Rensburg; Bernice Barnard-Jenkins; Marina Rautenbach (MDPI AG, 2021)
Candida species are highly adaptable to environmental changes with their phenotypic flexibility allowing for the evasion of most host defence mechanisms. Moreover, increasing resistance of human pathogenic Candida strains has been reported against all four classes of available antifungal drugs, which highlights the need for combinational therapies. Tyrocidines are cyclic antimicrobial peptides that have shown synergistic activity with antifungal drugs such as caspofungin and amphotericin B. However, these cyclodecapeptides have haemolytic activity and cytotoxicity, but they have been used for decades in the clinic for topical applications. The tyrocidines tend to form higher-order structures in aqueous solutions and excessive aggregation can result in variable or diminished activity. Previous studies have shown that the tyrocidines prefer ordered association to celluloses. Therefore, a formulation with soluble cellulose was used to control the oligomer stability and size, thereby increasing the activity against Candida spp. Of the formulants tested, it was found that commercial hydroxy-propyl-methyl cellulose, E10M, yielded the best results with increased stability, increased anti-Candida activity, and improved selectivity. This formulation holds promise in topical applications against Candida spp. infections.